Aardvarkian gothic. Issue 6 (2nd November 2017) - Grace, Dominick
ABSTRACT: Gothic motifs figure strongly in several storylines in Dave Sim's Cerebus series, albeit initially for predominantly parodic purposes. One of Sim's earliest multi-issue arcs, comprising issues 23–25, involves not merely parody of specific mainstream comic elements but also of gothic tropes. Sim's genre-bending is one of the strengths of Cerebus, and this arc demonstrates Sim's skill in weaving gothic elements into the book, for parodic purposes but also to serve Sim's gestational thematic interests. Sim exploits several characteristic elements of the gothic to trouble questions of gender and representation. He reverses the standard trope of the vulnerable woman in a mysterious space, threatened explicitly with violence and implicitly with sex, by making the male Cerebus the vulnerable figure, surrounded by sexually tempting adolescent girls. The story further complicates questions of gender in its invocation of drag, climaxing its interrogation with an innovative take on the doppelgänger motif by introducing Woman Thing and Sump Thing as parodic monstrous others whose violent/sexual encounter literalises Sim's sexual politics, not to mention the crisis of representation sometimes seen as a key element of gothic. In doing so, he lays the groundwork for much of what will follow in Cerebus .